Kimia Medisinal dan Perannya Dalam Pengembangan Terapi Personalisasi - M, Maesaroh; Amin, Saeful (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Personalized therapy is a treatment approach that considers genetic, environmental, and lifestyle variations of each individual to optimize the effectiveness and safety of therapy. This study aims to analyze the role of medicinal chemistry in the development of personalized therapy through the perspective of rational design of drug molecules, structural modification, and optimization of pharmacokinetic-pharmacodynamic properties. The method used is a systematic literature review with the PRISMA approach to scientific publications in 2013-2023 that focus on the integration of medicinal chemistry with pharmacogenomics and personalized therapy. The results of the study showed that medicinal chemistry plays an important role in four main areas: (1) drug design based on specific genetic targets with high selectivity (76% of publications); (2) development of prodrugs and drug delivery systems that are responsive to individual biomarkers (63% of publications); (3) optimization of pharmacokinetics based on genetic variations of drug metabolizing enzymes (58% of publications); and (4) development of molecular probes for companion diagnostics (52% of publications). Further analysis identified the development trends of personalized therapy including multi-target drug design based on patient molecular profiles and big data-based medicinal chemistry strategies. The main challenges identified include the complexity of molecular modification to achieve pharmacokinetic profiles that match specific genetic subtypes and the limitations of experimental models that represent individual heterogeneity. In conclusion, medicinal chemistry plays a fundamental role in realizing the concept of personalized therapy through the design and optimization of drug molecules that match individual patient characteristics. Further research is needed for the development of medicinal chemistry methodologies integrated with omics technology and artificial intelligence to accelerate the translation of the concept of personalized therapy into real clinical applications in Indonesia.